A Synthetic Phased Array Surface Acoustic Wave Sensor for Quantifying Bolt Tension - ŞİŞMAN, ALPER (MDPI, 2012)
In this paper, we report our findings on implementing a synthetic phased array surface acoustic wave sensor to quantify bolt tension. Maintaining proper bolt tension is important in many fields such as for ensuring safe operation of civil infrastructures. Significant advantages of this relatively simple methodology is its capability to assess bolt tension without any contact with the bolt, thus enabling measurement at inaccessible locations, multiple bolt measurement capability at a time, not requiring data collection during the installation and no calibration requirements. We performed detailed experiments on a custom-built flexible bench-top experimental setup consisting of 1018 steel plate of 12.7 mm (1/2 in) thickness, a 6.4 mm (in) grade 8 bolt and a stainless steel washer with 19 mm (3/4 in) of external diameter. Our results indicate that this method is not only capable of clearly distinguishing properly bolted joints from loosened joints but also capable of quantifying how loose the bolt actually is. We also conducted detailed signal-to-noise (SNR) analysis and showed that the SNR value for the entire bolt tension range was sufficient for image reconstruction.
Keywords: bolt tension; real area of contact; non-destructive testing; surface acoustic wave sensor; synthetic phase array; ultrasonic imaging; CONTACT; JOINT; AREA